SYNTHESIS, THERMAL STUDIES AND CONVERSION DEGREE OF DIMETHACRYLATE POLYMERS USING NEW NON-TOXIC COINITIATORS - Alarcon, Rafael Turra [UNESP]; Cunha Holanda, Bruno Barreto da [UNESP]; Rinaldo, Daniel [UNESP]; Caires, Flavio Junior [UNESP]; Almeida, Marcos Vinicius de; Bannach, Gilbert [UNESP] (Soc Brasileira Quimica, 2017)
The aim of this paper is to replace toxic coinitiators (tertiary amines) by non-toxic compounds such as glycerol and inositol (polyalcohol) in dimethacrylate resins. For this purpose, mid infrared spectroscopy (MIR) was used to calculate the monomers' degree of conversion (%DC); as well as simultaneous Thermogravimetric Analysis - Differential Thermal Analysis (TGA-DTA) and Differential Scanning Calorimetry (DSC) were conducted to evaluate thermal stability, degradation steps, and thermal events. The use of different initiator systems did not modify the thermal events or the thermal stability of each of the dimethacrylate resins. Results show a substitution of system 2 (toxicity) by system 3 (low toxicity), which had a good conversion velocity and total conversion in some monomers, is plausible.
Keywords: thermal studies; photopolymerization; non-toxic coinitiator; conversion degree; tertiary amine